Stability boundary analysis in single-phase grid-connected inverters with PLL by LTP theory - Salis, Valerio; Costabeber, Alessando; Cox, Stephen M.; Zanchetta, Pericle; Formentini, Andrea (IEEE, 2018)
Stability analysis of power converters in AC net¬works is complex due to the non-linear nature of the conversion systems. Whereas interactions of converters in DC networks can be studied by linearising about the operating point, the extension of the same approach to AC systems poses serious challenges, especially for single-phase or unbalanced three-phase systems. A general method for stability analysis of power converters suitable for single-phase or unbalanced AC networks is presented in this paper, based on Linear Time Periodic (LTP) theory. A single-phase grid-connected inverter with PLL is considered as case study. It is demonstrated that the stability boundaries can be precisely evaluated by the proposed method, despite the non-linearity introduced by the PLL. Simulation and experimental results from a 10kW laboratory prototype are provided to confirm the effectiveness of the proposed analysis.